2019
DOI: 10.22564/rbgf.v37i1.1992
|View full text |Cite
|
Sign up to set email alerts
|

The Nanosatc-Br, Cubesat Development Program - A Joint Cubesat Program Developed by Ufsm and Inpe/McTic - Space Geophysics Mission Payloads and First Results

Abstract: ABSTRACT.  The INPE-UFSM’s NANOSATC-BR, CubeSats Development Program started in 2008. Currently, the Program counts with two CubeSats: the NANOSATC-BR1 (1U) launched in 2014 and still in operation & the NANOSATC-BR2 (2U), under development, which is expected to be launched in the last quarter of 2019. In this article, the scientific and technological results of the NANOSATC-BR1 and the finalization of NANOSATC-BR2 are presented. Considering the Capacity Building, the major target of the Program, the paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Therefore, more than ever, a robust understanding of the positive and negative ionospheric storms is important in the anomalously low geomagnetic field intensity region currently located in South America known as South American Magnetic Anomaly (SAMA; Abdu et al., 2005; Kurnosova et al., 1962). In addition to positive/negative phases observed in the electron density that may cause problems in satellites, the large high‐energy particles that penetrate in the ionosphere may cause problems in satellite sensors (Schuch et al., 2019). It was also reported that the operator who controls satellites in low‐Earth orbit may need to turn sensors off to reduce the detector saturation when passing through the SAMA (Jones et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more than ever, a robust understanding of the positive and negative ionospheric storms is important in the anomalously low geomagnetic field intensity region currently located in South America known as South American Magnetic Anomaly (SAMA; Abdu et al., 2005; Kurnosova et al., 1962). In addition to positive/negative phases observed in the electron density that may cause problems in satellites, the large high‐energy particles that penetrate in the ionosphere may cause problems in satellite sensors (Schuch et al., 2019). It was also reported that the operator who controls satellites in low‐Earth orbit may need to turn sensors off to reduce the detector saturation when passing through the SAMA (Jones et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During space weather conditions as defined by Denardini et al (2016), elevated flux levels of high energetic particles may precipitate in the ionosphere in regions of anomalously weak geomagnetic field strength such as the South America Magnetic Anomaly (SAMA). Besides enhancing the ionization distribution and conductivities (Moro et al, 2013(Moro et al, , 2012, the energetic particles create high background counts which render satellite sensors unusable in this region (Schuch et al, 2019;Heirtzler, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The model describes monthly averages of the electron density, electron and ion temperature, total electron content (TEC), and ion composition as a function of height, location, and local time. Several major milestone editions of IRI have been released by the IRI Working Group since the 1970s in order to constantly revise the model to keep it as up to date and accurate as possible (Rawer et al, 1978a(Rawer et al, , b, 1981Bilitza, 1990Bilitza, , 2001Bilitza and Rawer, 1996;Bilitza and Reinisch, 2008;Bilitza et al, 2014Bilitza et al, , 2017. The latest version is known as IRI-2016 and has important improvements over the and 2007versions (IRI-2012and IRI-2007.…”
Section: Introductionmentioning
confidence: 99%
“…The term foF2 CCIR stands for the monthly average of the foF2 modeled by the CCIR sub-routine, while the term foF2 Observed is the monthly average of foF2 measured by the SMK29. Besides the comparison between the observed foF2 with CCIR, the sub-routine URSI (Rush et al, 1989) is also tested and, therefore, Eq. (1) is also used considering foF2 URSI instead of foF2 CCIR .…”
Section: Introductionmentioning
confidence: 99%